1995
DOI: 10.1002/poc.610080108
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects for the BF3‐mediated reactions of allyltributyltin and allyltriethyllead with benzaldehyde

Abstract: Substituent effects were measured for the reactions of substituted benzaldehydes with allyltributyltin (1) and allyltriethyllead (2) reagents in the presence of BF,*OEt, in CH,CI,. The Hammett p values were small and positive at 25°C and negative at -78°C for both 1 and 2. These could be interpreted in terms of the contribution of electrophilic complexation between the aldehyde function and BF, as a rate-limiting step. A large negative p value was observed for the complex-formation equilibria between substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[1,2] The literature is rife with examples of reaction pathways in which reactants, intermediates, and products, as well as their associated transition states, are cartooned as a series of static geometries each possessing a specific reaction enthalpy. Often, a picture of this type successfully captures the key aspects of a system allowing, for example, identification of the primary mechanistic pathway [3][4][5][6][7][8][9] or rationalization of the presence of a specific intermediate. [9][10][11][12][13] Such descriptions, however, are occasionally insufficient to chemistry occurring in an experimental setting, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] in the most extreme cases leading to disastrous failures.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The literature is rife with examples of reaction pathways in which reactants, intermediates, and products, as well as their associated transition states, are cartooned as a series of static geometries each possessing a specific reaction enthalpy. Often, a picture of this type successfully captures the key aspects of a system allowing, for example, identification of the primary mechanistic pathway [3][4][5][6][7][8][9] or rationalization of the presence of a specific intermediate. [9][10][11][12][13] Such descriptions, however, are occasionally insufficient to chemistry occurring in an experimental setting, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] in the most extreme cases leading to disastrous failures.…”
Section: Introductionmentioning
confidence: 99%
“…The initial complex formation is an electrophilic reaction of BH 3 , and thus a ρ value on this equilibrium should be negative. Indeed, it was reported that the Hammett ρ value for the complex‐formation equilibrium between 1‐X and BF 3 in CH 2 Cl 2 was largely negative (−3.5 at −78 °C) . Although BF 3 is a much stronger acid and therefore forms a much stronger complex with aldehyde than BH 3 , the result clearly indicated that the complex formation is a strongly electrophilic process.…”
Section: Resultsmentioning
confidence: 95%
“…[3] The energetics of the CCl 2 -cyclopropene systemthat is, a near-negligible barrier to addition (<2 kcal/mol), substantial exothermicity (ΔH = −65 to −78 kcal/mol to form 2; ΔH = −83 to −106 kcal/mol to form 5), and post-TS branching of the reaction pathsled us to propose that CCl 2 addition to cyclopropene, and therefore the experimental product ratio, is controlled by nonstatistical reaction dynamics. [3] Previous instances of a single TS leading to multiple products [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] on a potential energy surface containing a plateau [20][21][22][23][24][25][26][27] have been attributed to dynamic control [28][29][30][31][32][33] of these reactions as well.…”
Section: Introductionmentioning
confidence: 99%